Of thee I sing : a letter to my daughters - Obama, Barack; Long, Loren (New York : Alfred A. Knopf, 2010)
"In this tender, beautiful letter to his daughters, President Barack Obama has written a moving tribute to thirteen groundbreaking Americans and the ideals that have shaped our nation. From the artistry of Georgia O'Keeffe, to the courage of Jackie Robinson, to the patriotism of George Washington, President Obama sees the traits of these heroes within his own children, and within all of America's children"--Jacket.
Keywords: Conduct of life -- Juvenile literature; Virtues -- Juvenile literature; Individual differences -- Juvenile literature; Respect for persons -- Juvenile literature; Heroes -- United States -- Juvenile literature; National characteristics, American -- Juvenile literature; United States -- History -- Juvenile literature; Conduct of life; Virtues; Respect for persons; Heroes; National characteristics, American; United States -- History; Conduct of life -- Juvenile literature; Virtues -- Juvenile literature; Individual differences -- Juvenile literature; Respect for persons -- Juvenile literature; Heroes -- United States -- Juvenile literature; National characteristics, American -- Juvenile literature; United States -- History -- Juvenile literature; United States -- History